Survival of probiotics Lactobacillus acidophilus TISTR1338 in a synbiotic-supplemented plant-based protein powder under various pH and temperatures - Ardsiri, Panisa; Chaoruangrit, Araya; Pongsetkul, Jaksuma; Bavisetty, Sri Charan Bindu; Piewthongngam, Kullapapruk; Sae-Eaw, Amporn; Petsong, Kantiya (My University, 2024)
The demand of plant-based protein has been remarkably increased, leading to the development of various plant-based protein products. Supplementation of synbiotic is an effective approach to improve food function. This study aimed to develop the formulation of plant-based protein product supplemented with synbiotic which provides high survivability of probiotic through various harsh conditions. Pea protein isolate (PPI), inulin, and glycerol at ratio 2:1:1 was supplemented with probiotic strain (Lactobacillus acidophilus TISTR1388) to develop as encapsulated synbiotic plant-based protein powder (SPBP). The developed formulation provided probiotic survival rate after freeze-drying and gastro-intestinal (GI) tract conditions at 95.0±2.1% and 62.4±6.1%, respectively. Whereas, probiotic as free-cells showed survival rate after freeze-drying at 78.9±0.4% and no survival cell was observed after GI tract digestion. Scanning Electron Microscope (SEM) analysis demonstrated SPBP's remarkable capacity to perfectly entrap probiotic cells with no visible cell damage. Herein, the stability of the SPBP was tested through various pH levels (3, 5, 7, and 9) and temperature levels (6±2°C, 26±2°C, and 55±2°C) in order to investigate the possibility of applying this product to various food categories. Results showed that developed SPBP survived through all tested pH and temperature levels for 3 h at least 88.9±6.6%. Shelf-life evaluation showed that SPBP provided survival rate of probiotic cells up to 96.2±2.4% an aw of 0.09±0.01 after 12 weeks of refrigerated storage. Overall, results revealed that SPBP had a strong possibility of being employed as a probiotic stabilizer that may be further developed for a functional food product.
Keywords: Encapsulation; Harsh conditions; Plant-based protein powder; Stability; Synbiotic